Design and analysis of a wide band rectangular slot loaded planer microstrip antenna - Gaurav Mishra, Raj; Mishra, Ranjan; Kuchhal, Piyush (International Journal of Engineering and Technology, 2018)
This paper presents design and analysis of a rectangular planar microstrip antenna for high bandwidth. The proposed antenna is rectangular in shape with a rectangular slot on the center of patch. The antenna is designed and fabricated with FR4 epoxy substrate. The simulated and experimental results are giving a wide bandwidth of in excess of 4.5 GHz. The measured result also validate the simulate design. A simple analysis is also carried out and impedance is calculated.